1 Records of the Governor and Company of the Massachusetts Bay 211-12 (1853) - (:unkn) unknown (My University, 1637)
Whereas the opinions & revelations of Mr Wheeleright & Mrs Hutchinson have seduced & led into dangerous errors many of the people here New England , insomuch as there is just cause of suspicion that they, as others in Germany, in former times, may, upon some revelation, make some sudden irruption upon those that differ from them in judgment, for Prevention whereof it is ordered, that all those whose names are underwritten shall (upon warning given or left at their dwelling houses) before the 30th day of this month of November, deliver in at Mr Canes house, at Boston, all such guns, pistols, swords, powder, shot, & match as they shall be owners of, or have in their custody, upon pain of ten pound for ev§y default to bee made thereof; which arms are to be kept by Mr Cane till this Court shall take further order therein. Also, it is ordered, upon like penalty of [some unreadable amount of money, perhaps §, s., or p.), that no man who is to render his arms by this order shall buy or borrow any guns, swords, pistols, powder, shot, or match, until this Court shall take further order therein
Keywords: BILL OF ATTAINDER